Contribution à la reconnaissance de l’importance du Tabaculture dans la région du souf - SOUFLI, Wafa; BOUSBIA, Wijden; BEN BOUZID, Rachid (University of Eloued جامعة الوادي, 2023)
This study aims to define the importance of tobacco cultivation in the Oued Souf region. for this study we conducted a field investigation that included 40 agricultural investors distributed in 04 municipalities, in order to study all aspects related to tobacco cultivation in terms of agricultural and economic terms, as the questionnaire was based through its questions on an attempt to discover The agricultural techniques used in the areas cultivated with tobacco and the amount of production extracted, in addition to knowing the various obstacles and problems faced by the farmers of this division, whether they are problems related to agriculture per se or obstacles specific to the economic aspect, which negatively affect the tobacco crop. The obtained results showed that the samples included in the questionnaire, do not apply agricultural techniques as it should be, as most farmers are not interested in applying the agricultural rotation technique, in addition to the large use of organic and mineral fertilizers, which accounted for more than 25% of the production costs per hectare, while the percentage of production costs per hectare reached Watering 20, as well as labor for planting and harvesting the crop, cost approximately 20 percent. The results obtained showed that most of the farmers grow tobacco in the season under the pretext of appropriate conditions and abundance of production. Through our investigation, we found a number of problems facing farmers who practice tobacco cultivation in relation to the marketing of the crop, most of which are due to the laws imposed by the state’s economic policy on farmers, which narrowed the circle of marketing the bumper crop, which constituted a major obstacle for tobacco producers. Despite the great importance of tobacco cultivation in the Oued Souf region in economic terms, and the increase in the quantity of production by more than 60 percent of the national production, the farmers seek to improve the methods of practicing tobacco cultivation to increase production in terms of quantity and quality, asking the government to reconsider the laws and policy adopted to enable farmers to market The crop within the legal frameworks.
production végétale
Keywords: Tobacco cultivation - agricultural techniques - production cost - Valley state - economic importance; زراعة التبغ